Co-regulation of cell polarization and migration by caveolar proteins PTRF/Cavin-1 and caveolin-1. - Michelle M Hill (Public Library of Science (PLoS), 2012)
Caveolin-1 and caveolae are differentially polarized in migrating cells in various models, and caveolin-1 expression has been shown to quantitatively modulate cell migration. PTRF/cavin-1 is a cytoplasmic protein now established to be also necessary for caveola formation. Here we tested the effect of PTRF expression on cell migration. Using fluorescence imaging, quantitative proteomics, and cell migration assays we show that PTRF/cavin-1 modulates cellular polarization, and the subcellular localization of Rac1 and caveolin-1 in migrating cells as well as PKCα caveola recruitment. PTRF/cavin-1 quantitatively reduced cell migration, and induced mesenchymal epithelial reversion. Similar to caveolin-1, the polarization of PTRF/cavin-1 was dependent on the migration mode. By selectively manipulating PTRF/cavin-1 and caveolin-1 expression (and therefore caveola formation) in multiple cell systems, we unveil caveola-independent functions for both proteins in cell migration.